Kirkehistorie mellom det globale og det nasjonale - Rasmussen, Tarald (Dansk Teologisk Tidsskrift, 2018)
The new Danish two volume Church History aims at an integration of a global and a national perspective. The article discusses the handbook with a main focus on the theoretical perspectives applied in the text, including aspects like gender, confessional cultures and a comparative approach to Church History.